Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Indoline-based donor-pi-acceptor visible-light responsive organic dyes for dye-sensitized solar cells: co-sensitization with squaraine dye for panchromatic IPCE response - Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2022)
A series of metal-free indoline-based donor-pi-acceptor (D-pi-A) visible-light active organic dyes, where an indoline unit wrapped with alkyl or alkyl and glycolic (TEG) groups is used as a donor, a mono- or bi-thiophene unit is used as a pi-spacer, and cyanoacrylic acid acts as an acceptor unit, have been designed and synthesized for dye-sensitized solar cell (DSSC) application. These dyes showed three absorption bands in a dichloromethane solution: the first and second transitions are observed in the UV (337-385 nm) and visible (477-514 nm) regions and correspond to pi-pi* and intramolecular charge transfer (ICT) transition, respectively, whereas the third absorption band obtained in the near-IR (629-758 nm) region has been observed for the first time for a D-pi-A type dye architecture. Furthermore, the ICT transition band for AKT dyes showed negative solvatochromism with increasing polarity of solvents. Photovoltaic characterizations for AKT dyes have been systematically studied with a cobalt electrolyte to evaluate the effect of thiophene incorporation and alkyl group substitution by the TEG group on the DSSC device performance. Here, AKT2 showed the highest DSSC efficiency of 3.16% with V-OC of 0.680 V and J(SC) of 6.24 mA/cm(2) without chenodeoxycholic acid (CDCA) in the AKT dye series, whereas DSSC efficiencies for AKT dyes were not affected much upon further addition of CDCA. Furthermore, AKT dyes were co-sensitized with a complementary optical responsive indoline-based SQS4 dye and showed enhanced efficiency. The combination of AKT2/SQS4 dyes with a ratio of 1:1 showed a maximum of 5.20% co-sensitized solar cell efficiency compared to other dye combinations with the cobalt electrolyte.
Keywords: Dye-sensitized solar cells; indoline-based donor-pi-acceptor dye; intramolecular charge transfer; metal-free organic dye; panchromatic-light absorption; Solvatochromism